Diaphragm Thickening Fraction vs Rapid Shallow Breathing Index in Predicting Weaning Success: A Prospective Diagnostic Study - Deif Tunggal; I Gusti Ngurah Mahaalit Aribawa; Dewa Ayu Mas Shintya Dewi (Udayana University and Indonesian Society of Anesthesiologists (PERDATIN), 2026)
Introduction: Weaning from mechanical ventilation is a critical step in intensive care, and inaccurate assessment may increase the risk of complications. The rapid shallow breathing index (RSBI) is widely used to evaluate weaning readiness but does not directly assess diaphragmatic function. Diaphragm thickening fraction (DTF), measured by bedside ultrasound, has been proposed as an additional predictor of weaning success. This study aimed to compare the diagnostic performance of DTF and RSBI in mechanically ventilated ICU patients. Patients and Methods: This prospective diagnostic accuracy study was conducted in a tertiary hospital in Denpasar, Indonesia, from September to December 2022, in accordance with STARD 2015 guidelines. Adult patients aged 18–65 years who received invasive mechanical ventilation for >24 hours and were considered ready for weaning were included. RSBI and right-sided DTF were measured at the fifth minute of a spontaneous breathing trial. Weaning success was defined as extubation without reintubation, noninvasive ventilation, or death within 48 hours. Results: Fifty-six patients were included, of whom 73.2% achieved successful weaning. DTF demonstrated high sensitivity (95.4%) and moderate specificity (75.0%), with a positive predictive value of 93.3% and a negative predictive value of 81.8%. RSBI showed sensitivity of 97.5% and specificity of 80.0%, with higher discriminative performance (AUC 0.88 vs 0.79). Confidence intervals and statistical comparisons between AUCs were not performed. Conclusion: Both RSBI and DTF were associated with weaning success. RSBI demonstrated superior overall diagnostic performance and remains the primary assessment tool. DTF may provide additional physiological information on diaphragmatic function and serve as a complementary parameter during weaning assessment.